2019
DOI: 10.1155/2019/4296523
|View full text |Cite
|
Sign up to set email alerts
|

Association between Inflammatory Cytokine Levels and Thrombocytopenia duringPlasmodium falciparumandP. vivaxInfections in South-Western Coastal Region of India

Abstract: Background. Thrombocytopenia is a most commonly observed complication during malaria infections. Inflammatory cytokines such as IL-1, IL-6, and IL-10 have been documented in malaria induced thrombocytopaenia. This study was aimed to understand the possible relationship between inflammatory cytokines across varying degrees of thrombocytopenia duringP. vivax,P. falciparum,and mixed infections.Methods. A hospital-based cross sectional study was conducted at District Wenlock Hospital in Mangaluru, a city situated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 45 publications
9
27
0
Order By: Relevance
“…In this sense, one can claim that these inflammatory mediators may be contributing in different ways between moderate and severe thrombocytopenia and the progression is not necessarily linear in terms of mechanism. Against this, a recent hospital-based study involving a restrict number of cytokines suggested that inflammatory mediators may influence the transformation of mild forms of thrombocytopenia into severe forms (Punnath et al, 2019). Of note, this finding is also supported by our data showing that an increasing concentration of mediators linked to PvST in plasma correlated with a progressive decrease in the number of platelets in peripheral blood.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this sense, one can claim that these inflammatory mediators may be contributing in different ways between moderate and severe thrombocytopenia and the progression is not necessarily linear in terms of mechanism. Against this, a recent hospital-based study involving a restrict number of cytokines suggested that inflammatory mediators may influence the transformation of mild forms of thrombocytopenia into severe forms (Punnath et al, 2019). Of note, this finding is also supported by our data showing that an increasing concentration of mediators linked to PvST in plasma correlated with a progressive decrease in the number of platelets in peripheral blood.…”
Section: Discussionsupporting
confidence: 87%
“…Although the same regulatory mediators (IL-10/IL-1Ra/HGF) were included in the abovementioned panels that discriminate PvST from healthy controls or non-thrombocytopenic patients, decision trees confirmed the levels of IL-10 as critical to classify PvST as compared with controls. Previous studies supported a similar association between IL-10 and decreased blood platelet counts (Park et al, 2003;Coelho et al, 2013;Raza et al, 2014;Punnath et al, 2019).High levels of IL-10 are commonly observed in P. vivax infections and are primarily associated with the immune system's effort to counteract excessive inflammation (Andrade et al, 2010). This oversimplified association of IL-10 with less severe vivax disease has been challenged by studies that reported a lack of correlation between regulatory cytokines and milder symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…For this study, thrombocytopenia presented a negative correlation with parasitaemia (r − 0.2223, p 0.0220, data not shown), and was the most frequent finding in patients with liver dysfunction, similar to what was previously reported by other researchers ( Fazil et al, 2013 ; Martínez-Salazar and Tobón-Castaño, 2014 ). The mechanism involved in thrombocytopenia that is observed in patients with malaria is not clear, there are a variety of hypotheses that include platelet sequestration by the spleen during the removal of parasitized cells, platelet auto-aggregation, circulation of anti-platelet antibodies and the alteration in thrombopoietin synthesis that derives from the cytokines action (M. V. G. Lacerda et al, 2011 ; Punnath et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…(25) The cytokine imbalance in thrombocytopenia caused by vivax malaria has been reported by several studies without a consensus about which cytokines could be associated to thrombocytopenia. (4,13,20,26,27) In this study, we assessed immune responses in relation to other parameters as well as platelet counts. Of all the cytokines, only IL-1β, IL-12 and IL-2 differed in Pv-MAL patients, and were associated with increases in the PDW values.…”
Section: Discussionmentioning
confidence: 99%